Expectations versus experience: What do citizens demand when dealing with criminal courts? - Fernández Molina, Esther (Criminology & criminal justice, 2026)
There is a large body of evidence on how perceptions of procedural justice affect legitimacy and compliance. Despite the consistency of the findings, there is less research on the impact that citizens’ experiences with courts may have on public perceptions. This article examines this issue through an online survey of a national sample of Spanish citizens, controlling for the effects of the individual’s role in the process (defendant or victim) and membership of a vulnerable group. To this end, a two-dimensional measure of procedural justice was used. The results show that expectations towards the criminal justice system have differential effects, the quality of decision-making affects legitimacy and the quality of treatment affects compliance. Moreover, participation is a key element of satisfaction with the judicial experience, especially for defendants and members of minority groups. The findings are discussed within the framework of Tyler’s process-based model and concepts of anticipatory and hermeneutical injustice.